On errors of a unified family of approximation forms of bivariate continuous functions - Kao, Chung-Siung (Tamkang Journal of Mathematics, 2003)
Approximation forms for a regular bivariate functions f(x,y) were obtained by putting expectation on a convergent bivariate stochastic sequence for which some proper error bounds are herein derived to evaluate the applicability of the approximation forms when actually applied to be approximates of regular bivariate functions.